Testing for coeliac disease rarely leads to a diagnosis: a population-based study - Maxine D. Rouvroye; Lotte Oldenburg; Pauline Slottje; Johanna H. K. Joosten; Renee X. de Menezes; Marcel E. Reinders; Gerd Bouma (Taylor & Francis Group, 2021)
Background Coeliac disease (CD) has an estimated prevalence of ∼1% in Europe with a significant gap between undiagnosed and diagnosed CD. Active case finding may help to bridge this gap yet the diagnostic yield of such active case finding in general practice by serological testing is unknown. Objective The aim of this study was to determine (1) the frequency of diagnosed CD in the general population, and (2) to investigate the yield of active case finding by general practitioners. Methods Electronic medical records of 207.200 patients registered in 49 general practices in The Netherlands in 2016 were analysed. An extensive search strategy, based on International Classification of Primary Care codes, free text and diagnostic test codes was performed to search CD- or gluten-related contacts. Results The incidence of CD diagnosis in general practice in 2016 was 0.01%. The prevalence of diagnosed CD reported in the general practice in the Netherlands was 0.19%, and considerably higher than previously reported in the general population. During the one year course of the study 0.95% of the population had a gluten-related contact with their GP; most of them (72%) were prompted by gastrointestinal complaints. Serological testing was performed in 66% (n = 1296) of these patients and positive in only 1.6% (n = 21). Conclusion The number of diagnosed CD patients in the Netherlands is substantially higher than previously reported. This suggests that the gap between diagnosed and undiagnosed patients is lower than generally assumed. This may explain that despite a high frequency of gluten-related consultations in general practice the diagnostic yield of case finding by serological testing is low.Key points The diagnostic approach of GPs regarding CD and the diagnostic yield is largely unknown Case finding in a primary health care practice has a low yield of 1.6% CD testing was mostly prompted by consultation for gastrointestinal symptoms There is a heterogeneity in types of serological test performed in primary care